Avaliação da sobrevida e de marcadores histomorfológicos como potenciais fatores prognósticos para carcinoma de células escamosas em cães e gatos - Guim, Tainã Normanton (2010)
Squamous cell carcinoma (SCC) is a cutaneous malignant neoplasm commonly observed in dog and cat. Especially in our country, the SCC represents a serious problem, since chronic exposure to ultraviolet radiation is one of the important factors for the development of the disease. In this way, the objective of this study was establish histomorphological markers as prognostic factors and determine the time and the estimated survival of dogs and cats carriers of SCCs. A survey of cases of SCCs in dog and cat diagnosed at the Regional Diagnostic Laboratory from the Federal University of Pelotas, was performed during the period of 1999 to 2009. Fifty samples were obtained from biopsies and/or necropsies. From the studied cases, 24 animals with the disease were followed for a period of one year. In this study, we used the histological grade and survival time of animals as a criterion to prognostic evaluation. The histological parameters evaluated as peritumoral lymphoplasmacytic infiltration, tissue eosinophilia associated with tumor, mitotic index, arrangement, invasion to adjacent tissues, emboli vascular blood and/or lymphatic, desmoplastic reaction and quantification of AgNORs were confronted with the histological grade and the survival time of affected animals. When the histological parameters were compared with survival, a significant relation was observed with the intensity of invasion to adjacent tissues (p <0.05). When confronted with the histological grade, the invasion show significant results only to poorly differentiated SCCs and desmoplasia were statistically significant (p <0.05). In this study, the estimate of survival was 23.4% in one year to animals with or without treatment. From the results obtained, it was concluded that the intensity of invasion is an important predictive prognostic factor for cutaneous SCCs in dogs and cats. Other parameters showed no relation with the histological grade and/or survival, thus, are not considered prognostic factors predictive. The time and the estimate of survival were low and therefore the prognosis for dogs and cats carrier of cutaneous SCCs is unfavorable.